Meaning Construction in Print Beer Ads - Negro Alousque, Isabel; Cortés de los Ríos, M.ª Enriqueta (Miscelánea: A Journal of English and American Studies, 2018)
The aim of this study is to shed some light on the way meaning is constructed in print beer ads. The present paper lies within the scope of the research into the instantiation of metaphor, metonymy and image schemas in advertising. It analyses the role of these conceptual mechanisms from a contrastive perspective on the basis of an on-line corpus of English and French print beer ads. The theoretical underpinnings of this paper are based on the Cognitive Theory of Metaphor (Lakoff and Johnson 1980; Ruiz de Mendoza and Pérez 2011, among others) on the one hand, and the studies on multimodal metaphor (Forceville 1996, 2009, 2012, 2016; Forceville and Urios-Aparisi 2009) on the other, which have revealed that meaning is created through modes of communication other than verbal ones. The paper shows the role of monomodal and multimodal metaphor and metonymy as persuasive devices in advertising and the image-schematic basis of many metaphors and metonymies.
Keywords: metaphor; metonymy; image schema; advertising; persuasion